The effect of Self-Directed Learning on the relationship between Self-Leadership and Online Learning among university students in Turkey - Mehmet Durnali (Universidad de Deusto, 2020)
More and more people across the world seek a university education. Therefore, universities offer full or partial distance undergraduate and postgraduate degrees to meet that demand. Distance education has become more widespread with advances in the Internet and computer technologies and online learning and teaching software (e.g., Learning Management Systems). The spread of the Coronavirus disease (COVID-19), which broke out in early 2020, has also played a significant role in the increased popularity of distance education. Therefore, investigating and reporting upon university students' self-leadership (SL) behaviors, self-directed learning (SDL) skills, and online learning (OL) attitudes in such learning environments is both timely and critical. This empirical study used a relational survey model to investigate SL, SDL, and OL among university students. The sample consisted of 835 students in Turkey. Data were collected using the "Self-Directed Learning Scale (SDLS)," "Revised Self-Leadership Questionnaire (RSLQ)," and "Online Learning Attitude Scale (OLAS)." Data were analyzed using descriptive statistics, Pearson coefficient, Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). SL was moderately and positively correlated with SDL and OL. SDL was moderately and positively correlated with OL. SDL played a fully mediating role in the relationship between SL and OL. SL predicted OL in both the indirect and total effect model. This study addressed university students' perceptions and tested a model to provide empirical evidence for the relationships and predictions of SL, SDL, and OL. Therefore, it is believed that the results will help advance the constructs of SDL, SL, and OL paradigms. Received: 07 March 2020 Accepted: 17 November 2020